An empirical study on the determination of price, warranty length and production rate in the dynamic sales market. (31st October 2012) - Wu, Chin-Chun; Chou, Chao-Yu; Huang, Chikong; Lin, Yu-Chang
This paper provides a theoretical development and an empirical study on determining price, warranty length and production rate in the dynamic sales market, where word of mouth is important. For the theoretical development, we present a decision model of determining the optimal price, warranty length and production rate of a product such that the present value of the product profit may be maximised. The empirical study aims at choosing among the alternative model specifications and assessing the shapes of the sales rate function. The sales rate functions are estimated by non-linear regression, and then are tested by using automobile sales data in Taiwan as input while price, warranty length and production rate as outputs. The results of the empirical study are consistent with the corresponding theoretical predictions and consequently show the applicability of decision model.